Pelvic mass causing hematospermia: splenosis - Yu Jiang; Lei Chen; Min Wang; Xiaocan Li; Dongdong Xie; Dexin Yu; Yi Wang (BMC Urology, 2022)
Abstract Background Most patients with splenosis have no clinical symptoms and do not need intervention. Hematospermia and testicular pain occurred in this patient, which was considered to be related to the huge pelvic implantation of the spleen, which was relatively rare in clinical practice, so we hereby report this case. Case presentation A 28-year-old male patient with a history of splenectomy was admitted to the Urology Department of the Second Affiliated Hospital of Anhui Medical University with the chief complaint of "Hematospermia for 1 month and testicular pain for 2 days". Preoperative imaging examination indicated pelvic mass. Combined with the patient's history of splenectomy for splenic rupture in childhood, the possibility of pelvic spleen implantation was considered. Laparoscopic pelvic exploration was performed. During the operation, multiple grayish-brown nodular tissues were observed in the space between the posterior bladder and rectum, and a lobulated grayish-brown mass with a diameter of about 9 cm was observed in the posterior upper part of the prostate gland and seminal vesicle at the pelvic floor. Two nodular tissues were removed intraoperatively and sent for quick frozen pathology, which was reported as spleen tissue. Further resection of the huge mass was performed, and the postoperative pathological results were consistent with the diagnosis of splenosis. Conclusion We report a rare case of splenosis presenting with hemospermia and testicular pain.